Os direitos sociais do trabalho e a reforma trabalhista sob a ótica do direito econômico - Silva, Verônica de Lima (2021)
Currently, there is a global economy that has been greatly affected by countless transformations in the social, political and economic field, thus causing the world crisis that has driven the adoption of a neo-liberal policy, supported by market reforms with the objective of promoting an economic reconstruction on a big scale. Brazil, in the last five years, has also suffered the impact of a mutating global economy, as well as facing internal political and economic transformations, investing in reforms: labor and social security, as measures to face the internal economic crisis. The focus of this research consists in the case-by-case analysis of the changes pushed with the labor reform under the constitutional aspect of social and economic rights, which justify in the foreground the possible suppression of social rights, in the background the seeming mitigation of labor rights and lastly verify possible offenses against the constitutional order. The current study uses the hypothetical-deductive method, aided by bibliographical revision research and supported by books, laws, treaties, declarations, international conventions, articles, journalistic materials and recent jurisprudence established in the field of legal science focused on social labor rights and the constitutional order. As a result, it is possible to verify that the labor reform resulted in the precariousness of labor relations, with the flexibilization of the work contract, working hours, reduction of wages, weakening of union entities due to the disconnection in individual and collective negotiations and, finally, the access restriction to justice. It is concluded that the changes promoted by the labor reform were carried out overlapping the social rights, formerly enshrined in the Federal Constitution of Brazil, relativizing the importance of social labor law to the economic order.